Inositol-Requiring Enzyme 1 Alpha Endoribonuclease Specific Inhibitor STF-083010 Alleviates Carbon Tetrachloride Induced Liver Injury and Liver Fibrosis in Mice - Chen, Qian-Qian; Zhang, Cheng; Qin, Ming-Qiang; Li, Jian; Wang, Hua; Xu, De-Xiang; Wang, Jian-Qing (Frontiers in Pharmacology, 2018)
Accumulating data demonstrated that hepatic endoplasmic reticulum (ER) stress was involved in the pathogenesis of liver fibrosis. Long-term chronic hepatocyte death contributed to liver fibrosis initiation and progression. Previous researches reported that ER stress sensor inositol-requiring enzyme 1 alpha (IRE1α) was first activated in the process of liver fibrosis. STF-083010 was an IRE1α RNase specific inhibitor. This study aimed to explore the effects of STF-083010 on carbon tetrachloride (CCl4)-induced liver injury and subsequent liver fibrosis. Mice were intraperitoneally (i.p.) injected with CCl4 (0.15 ml/kg) for 8 weeks. In STF-083010+CCl4 group, mice were injected with STF-083010 (30 mg/kg, i.p.), twice a week, beginning from the sixth week after CCl4 injection. CCl4 treatment markedly enhanced the levels of serum ALT, TBIL, DBIL and TBA, and STF-083010 had obviously extenuated CCl4-induced exaltation of ALT, DBIL and TBA levels. CCl4-induced hepatic hydroxyproline and collagen Ι, major indicators of liver fibrosis, were alleviated by STF-083010. Additionally, CCl4-induced α-smooth muscle actin, a marker for hepatic stellate cells activation, was obviously attenuated in STF-083010-treated mice. Moreover, CCl4-induced upregulation of inflammatory cytokines was suppressed by STF-083010. Mechanistic exploration found that hepatic miR-122 was downregulated in CCl4-treated mice. Hepatic MCP1, CTGF, P4HA1, Col1α1 and Mmp9, target genes of miR-122, were upregulated in CCl4-treated mice. Interestingly, STF-083010 reversed CCl4-induced hepatic miR-122 downregulation. Correspondingly, STF-083010 inhibited CCl4-induced upregulation of miR-122 target genes. This study provides partial evidence that STF-083010 alleviated CCl4-induced liver injury and thus protected against liver fibrosis associated with hepatic miR-122.